Getting started dBase III plus. (Manila, Philippines : Pernik Printing Corp., 1986)
dBASE III PLUST$1!" (Bis a program that helps you collect and manage information or data. The data you enter is stored in a data- base. You can display, change, find, rearrange, analyze, relate, and print any data in your database. There are two ways to use dBASE III PLUS. The first is through The Assistant, a collection of menus you can use to accomplish most of your day-to-day data management tasks. The second is using dBASE III PLUS commands that allow you to perform directly any operation you select.s
Chapter 1. Quick start -- Chapter 2. Entry forms -- Chapter 3. Updating records -- Chapter 4. Searching and indexing -- Chapter 5. Queries -- Chapter 6. Reports and labels -- Chapter 7. Relating data -- Chapter 8. Import/export -- Chapter 9. dBASE III plus command -- Chapter 10. Creating and using program files.
Keywords: DBASE III